Reconstructing Penta-Helix: A Study of A Literature Review - Palestho, Andrea Basworo; Octanisa, Dheanita Sekarini (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2023)
This study is a literature review on the Penta-helix in tourism studies, which focuses on dialectical discussions to reconstruct the Penta-helix and generate new ideas. The literature review in this study uses a narrative review to describe each article that has been reviewed and to yield the essence of the papers. The result of this study constructed a new model for the implementation of the five tourism stakeholders, namely the Deep Penta-helix. This model uses the awareness and perspective of local communities to implement tourism development and tourism management.